A review of legislation in the sphere of energetics - M.A. Zhelaev (Ученые записки Казанского университета: Серия Гуманитарные науки)
An overview of the main regulations, by which public relations in the energetics sector are controlled, has been performed. The structure and main provisions of the regulations at the Russian (federal laws, decrees of the Government of the Russian Federation) and international (the Treaty on the Eurasian Economic Union) levels have been analyzed. Attention has been paid to the legislation establishing liability for the delinquency in this sphere (rules of the Code of the Russian Federation on Administrative Offenses and the Criminal Code of the Russian Federation). The analysis is based on the regulations on the behavior of the parties, both in the wholesale energy and retail market. The statistical data on lawmaking activity in the energy sector for the period of 2014–2018 have been given. It has been concluded that the number of regulations on the relations in this area is growing steadily, which, in turn, indicates a high interest of the state authorities in guiding the energetics sector.